A PERSONALIZED APPROACH TO ADJUVANT CHEMOTHERAPY FOR NON-SMALL CELL LUNG CANCER AFTER RADICAL SURGICAL TREATMENT BASED ON MOLECULAR MARKERS OF CHEMOSENSITIVITY - L. A. Efteev; E. O. Rodionov; S. V. Miller; S. A. Tuzikov; M. M. Tsyganov; I. V. Deryusheva; N. V. Litvyakov; I. G. Frolova (Сибирский онкологический журнал, 2019)
Despite advances in the treatment of non-small cell lung cancer (NSC LC), prognosis of advanced lung cancer is extremely poor. The search for additional treatment options to prevent local recurrence and distant metastases is of great importance. Monoresistance genes, such as ABCC5, BRCA1, RRM1, ERCC1, TOP1, TOP2a, TUBB3, and TYMS play a significant role in tumor sensitivity to chemotherapy for NSC LC. The expression levels of these genes in tumor tissue should be assessed for personalization of adjuvant chemotherapy in patients with NSC LC.Case description. We present a clinical case of a 65-year-old patient diagnosed with non-small cell lung cancer who underwent extended combined surgery followed by 4 courses of personalized adjuvant chemotherapy. The expression levels of monoresistance genes (ABCC5, RRM1, ERCC1, TOP1, TOP2a, TUBB3, BRCA 1 and TYMS) determined by reverse-transcriptase quantitative real-time PCR (RTqPCR) were used as predictive markers of response to adjuvant chemotherapy regimen.Conclusion. Our case report demonstrated the feasibility of performing organ-preserving surgery followed by personalized adjuvant chemotherapy based on the expression levels of monoresistance genes as predictive markers of benefit from adjuvant chemotherapy.